Study of the microstructure and oxidation behavior of YSZ and YSZ/Al2O3 TBCs with HVOF bond coatings - Karaoglanh, Abdullah Cahit (Materiali in tehnologije, 2012)
A significant improvement in efficiency has been achieved by using thermal barrier coatings (TBCs) in gas turbines and diesel engines. A typical TBC is a multilayered coating system that comprises an oxidation-resistant metallic bond coating (BC) and a thermally insulating ceramic top coating (TC). Under service conditions an Al2O3 inter-layer, the thermally grown oxide (TGO), forms in the interface between the bond and the top coating, by a chemical reaction between the metallic aluminum from the BC material and the oxygen that comes from the environment through the pore channels of the TC. The aim of the present study is to describe the TGO formation on metallic bond coats deposited using the high-velocity oxygen fuel (HVOF) spraying technique. Therefore, TBCs that consist of a YSZ top (ZrO2 + 8 % Y2O3) and YSZ-Al2O3 double-layer systems with CoNiCrAlY bond coats were deposited on Inconel 718 super-alloy substrates. The bond coats were applied via HVOF, with the ceramic top coats being applied by atmospheric plasma spraying (APS) as well. The oxidation behaviors of the TBC systems were investigated. The oxidation tests were performed at 1000 °C in an air atmosphere for (8, 24, 50) h. The formation and growth of the TGO layers and the microstructural changes during the oxidation tests were scrutinized systematically. The results indicate that the TBC coating with the YSZ-Al2O3 double layer had a higher oxidation resistance and a lower TGO layer growth than that of the traditional TBC system. Likewise, the initial state of the porosity plays a critical role in enhancing or limiting the growth of the TGO scale in the TBC.
Keywords: ceramic; keramika; toplotne zaščitne prevleke; oksidacija; atmosfersko plazemsko nabrizgavanje